1987
DOI: 10.1128/iai.55.8.1806-1812.1987
|View full text |Cite
|
Sign up to set email alerts
|

Structural and antigenic properties of lipopolysaccharides from serotype reference strains of Campylobacter jejuni

Abstract: To investigate the molecular basis for heat-stable antigenic diversity in Campylobacter jejuni, lipopolysaccharides (LPSs) from serotype reference strains and serotyped isolates were examined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis coupled with silver staining and immunoblotting. By silver staining, only low-Mr components, consisting of one major band and as many as three minor bands ranging in Mr from 4,500 to 5,000, were detected. However, by immunoblotting with homologous antisera, 10 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
3

Year Published

1990
1990
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 33 publications
6
77
0
3
Order By: Relevance
“…Although the PHA method will be most ef®cient for soluble antigens it had been assumed that the C. jejuni heat stable antigens were lipopolysaccharide (LPS) (Penner and Hennessey 1980). While long-chain LPS has been detected in some serotypes of C. jejuni (Preston and Penner 1987;Moran and Penner 1999 7 ), only LPS core and short-chain polysaccharides have been detected in other studies (Logan and Trust 1984) and it has been suggested that the antigen detected by PHA and direct agglutination is capsular (Chart et al 1996). Genetic studies on the Campylobacter genome have iden-ti®ed loci for both LPS/LOS and`capsule' 8 , Parkhill et al 2000.…”
Section: Serotypingmentioning
confidence: 99%
“…Although the PHA method will be most ef®cient for soluble antigens it had been assumed that the C. jejuni heat stable antigens were lipopolysaccharide (LPS) (Penner and Hennessey 1980). While long-chain LPS has been detected in some serotypes of C. jejuni (Preston and Penner 1987;Moran and Penner 1999 7 ), only LPS core and short-chain polysaccharides have been detected in other studies (Logan and Trust 1984) and it has been suggested that the antigen detected by PHA and direct agglutination is capsular (Chart et al 1996). Genetic studies on the Campylobacter genome have iden-ti®ed loci for both LPS/LOS and`capsule' 8 , Parkhill et al 2000.…”
Section: Serotypingmentioning
confidence: 99%
“…To detect the LPS, the samples were digested with proteinase K in PBS for 12 hr at 37 C and then were electrophoresed. In addition, the gel was fixed and stained with silver nitrate (20).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of strains were long known to express side chain-de®cient, low molecular weight outer membrane antigens of the lipo-oligosaccharide (LOS) type. In a minority (about one-third) of serotype strains a high molecular weight, protease-stable antigen capable of ladder formation on gel electrophoresis and Western blotting, characteristic of the presence of extended side chain or O-antigen of smooth lipopolysaccharide (LPS 2 ), was found (Preston and Penner 1987). The chemistry of the core structures of a number of these antigens has been explored extensively (reviewed by Fry et al 1998 andMoran andPenner 1999), indicating that the LOS type of structure has potential for expression of antigenic diversity.…”
Section: Polysaccharidesmentioning
confidence: 99%